We Aren’t All Integrationists: A Radical Critique of Racial School Integration - Wheeler-Bell, Quentin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2023)
Since the Second World War, racial integration has been the dominant way of framing racial justice. Those who advocate integration believe that racial justice would be achievable if Blacks were given an equal opportunity to compete on par with Whites. However, racial integration was critiqued most radically and vocally during the 1970s and early 1980s Black Power era. While the Black Power movement never coalesced into a unified critique of integration, it radically shifted debates within the Black public sphere. The attack on Black radicalism and the rise of neoliberalism combined to create a condition in which critiques of capitalism and demands for radical social transformation were increasingly seen as outdated, irrelevant, or a promotion of totalitarianism. This paper focuses on how the ideology of integration manifests in Derrick Darby and John Rury’s (2018) book, The Color of Mind. The ideology of integration is the hegemonic system of explicitly or tacitly held beliefs that misrepresents significant aspects of social reality by assuming that racial justice is solely, or even primarily, about integrating Blacks and other racialized groups into liberal capitalism. Darby and Rury reproduce the ideology of integration by framing racial justice as a fight for integration. To move beyond the ideology of integration, we must seriously engage the Black radical tradition, which requires philosophically reconstructing reasonable, but radical arguments within the Black radical tradition.